2019
DOI: 10.1186/s12913-019-4567-2
|View full text |Cite
|
Sign up to set email alerts
|

Prioritization approaches in the development of health practice guidelines: a systematic review

Abstract: Background Given the considerable efforts and resources required to develop practice guidelines, developers need to prioritize what topics and questions to address. This study aims to identify and describe prioritization approaches in the development of clinical, public health, or health systems guidelines. Methods We searched Medline and CINAHL electronic databases in addition to Google Scholar. We included papers describing priorit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 23 publications
(73 reference statements)
1
30
0
Order By: Relevance
“…• Prioritization criteria; we used a common framework of prioritization criteria that we developed for a recent systematic review on prioritization approaches in the development of health practice guidelines [24] (see S5 File).…”
Section: Data Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…• Prioritization criteria; we used a common framework of prioritization criteria that we developed for a recent systematic review on prioritization approaches in the development of health practice guidelines [24] (see S5 File).…”
Section: Data Synthesismentioning
confidence: 99%
“…A recent systematic review highlighted the opportunity to engage diverse types of stakeholders in prioritizing guideline topics [24]. Incorporating views of various stakeholders in guideline development can potentially reduce a biased selection of topics by few groups and increase transparency [7,31].…”
Section: Interpretation Of Findingsmentioning
confidence: 99%
“…The team then conducted a priority setting exercise to prioritize one of those topics. [13,14] The factors considered for priority setting included: public health burden; avoidable mortality and morbidity; economic burden on the health care system and patient; emerging diseases or emerging care options; potential impact of intervention on health outcomes, economy, health care system, and equity; variation in clinical practice; and rapidly changing evidence. [13,14] Eventually, the project team prioritized the topic of breast cancer screening as it was rated the highest.…”
Section: Prioritization Of the Topicmentioning
confidence: 99%
“…In fact, following a recent review of prioritisation exercises in published guidelines [10,11], the authors identified 11 steps of prioritisation that were used by guideline developers and noted that these steps are used inconsistently across published studies [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, following a recent review of prioritisation exercises in published guidelines [ 10 , 11 ], the authors identified 11 steps of prioritisation that were used by guideline developers and noted that these steps are used inconsistently across published studies [ 10 , 11 ]. This lack of a standardised process may produce guidelines that are not relevant for end-users or do not address their clinical needs.…”
Section: Introductionmentioning
confidence: 99%